2022
DOI: 10.1158/0008-5472.can-22-1740
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibition Induces Synthetic Lethality and Adaptive Immunity in LKB1-Mutant Lung Cancer

Abstract: Contradictory characteristics of elevated mutational burden and a “cold” tumor microenvironment (TME) coexist in LKB1-mutant non-small cell lung cancers (NSCLC). The molecular basis underlying this paradox and strategies tailored to these historically difficult-to-treat cancers are lacking. Here, by mapping the single-cell transcriptomic landscape of genetically engineered mouse models with Kras versus Kras/Lkb1 driven lung tumors, we detected impaired tumor-intrinsic IFNγ signaling in Kras/Lkb1 driven tumors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Here, we demonstrated a critical role for IFN-γ/STAT1/STAT3 signaling in regulating PARP1 levels in HGSOC cells, in line with our recent results in cervical cancer [17], and with the emerging evidence on the functional interplay between the STATs signaling cascade and PARP1 [28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we demonstrated a critical role for IFN-γ/STAT1/STAT3 signaling in regulating PARP1 levels in HGSOC cells, in line with our recent results in cervical cancer [17], and with the emerging evidence on the functional interplay between the STATs signaling cascade and PARP1 [28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…Of note, it has become increasingly clear that PARP1 may act as a crucial regulator of STAT1/STAT3 transcriptional activity, although the results are not consistent. Specifically, it has been reported that when PARP1 is aberrantly activated in cancer cells, it blocks phosphorylation of STAT1 and STAT3 via the poly(ADP-ribosyl)ation, ultimately reducing their transcriptional activity [ 28 , 31 ]. In line with these findings, Martincuks and colleagues [ 30 ] showed that PARPi treatment promotes STAT3 activation in ovarian cancer cells, tumor-associated immune cells and fibroblasts, resulting in PARPi resistance and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…STK11 plays a crucial role in regulating cell damage repair, energy metabolism, and tumor immune responses[ 16 ]. The LKB1 protein comprises three major domains: The N-terminal non-catalytic domain (encoded by amino acids 1-49), the catalytic kinase domain (encoded by amino acids 49-309), and the C-terminal non-catalytic regulatory domain (encoded by amino acids 309-433)[ 1 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous PARP1 inhibition and LKB1 loss can restore IFNγ signaling and transform the "cold" TME into a "hot" one, enhancing the effectiveness of immune therapies such as PD-1 blockade. 243 Therefore, under gene mutation in tumor cells, combining ICB therapy with the immune system is one of the future development directions of synthetic lethal therapy. These new approaches may bring intercell genetic interactions and non-cell-autonomous mechanisms into SL definition.…”
Section: Sl Drugs Combined With Immunotherapymentioning
confidence: 99%
“…The mutant LKB1 led to DNA repair deficiency and excessive activation of PARP1, which reduces the STAT1 activity and inhibits the IFNγ pathway. Simultaneous PARP1 inhibition and LKB1 loss can restore IFNγ signaling and transform the “cold” TME into a “hot” one, enhancing the effectiveness of immune therapies such as PD‐1 blockade 243 . Therefore, under gene mutation in tumor cells, combining ICB therapy with the immune system is one of the future development directions of synthetic lethal therapy.…”
Section: The Combination Of Antitumor Therapies Based On Slmentioning
confidence: 99%